2013
DOI: 10.1208/s12248-013-9460-z
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Organic Cation Transporter Polymorphisms on the Population Pharmacokinetics of Metformin in Healthy Subjects

Abstract: Abstract. This study investigated the effects of genetic polymorphisms in organic cation transporter (OCT) genes, such as OCT1-3, OCTN1, MATE1, and MATE2-K, on metformin pharmacokinetics. Of particular interest was the influence of genetic polymorphisms as covariates on the variability in the population pharmacokinetics (PPK) of metformin using nonlinear mixed effects modeling (NONMEM). In a retrospective data analysis, data on subjects from five independent metformin bioequivalence studies that used the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
(72 reference statements)
2
60
0
Order By: Relevance
“…Metformin is a substrate of various types of xenobiotics transporters including OCT1, OCT2, and MATEs,3–7 but there has been no information on possible transport of metformin by OCTN1. Yoon et al20 have recently reported that OCTN1 genetic variation affects pharmacokinetics of metformin. This report may be compatible with the present hypothesis that metformin is a substrate of OCTN1, but did not directly demonstrate the transport of metformin by OCTN1.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a substrate of various types of xenobiotics transporters including OCT1, OCT2, and MATEs,3–7 but there has been no information on possible transport of metformin by OCTN1. Yoon et al20 have recently reported that OCTN1 genetic variation affects pharmacokinetics of metformin. This report may be compatible with the present hypothesis that metformin is a substrate of OCTN1, but did not directly demonstrate the transport of metformin by OCTN1.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal-facing MATE1 and MATE2-K work in concert with OCT2 to mediate active renal secretion of basic drugs [51,56,87,88] (Figure 1). The roles of OCT2 and the MATE transporters in renal elimination of organic cations are well established [72,8991]. Many cationic drugs, such as metformin and atenolol, are eliminated by active renal secretion by the OCT2/MATE pathway [66,90,92].…”
Section: Impact Of Octs and Mates On Intracellular Levels Pharmacmentioning
confidence: 99%
“…Modeling was dependent upon the meticulous selection of an applicable pK model that is based on the bolus dose and duration of absorption of CBZ available from the in vivo plasma concentration–time profiles. A noncompartmental pK model was selected because it minimizes any assumptions in data modeling and undertaken with minimum interventions by the investigator while the rules of calculus are defined before the analysis particularly for potentially variable study settings as with the relatively prolonged transbuccal administration of CBZ . Before the pK model fitting of the in vivo data, WinNonlin® was used to accurately derive the initial parameter estimates to establish the need for necessary modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The terminal first order rate constant, lamda z ( λ z ), apparent volume of distribution ( V z ), maximum plasma concentration ( C max ), time required to attain C max ( T max ), average total time that CBZ molecules spent in the body post administration known as the mean residence time and average time required for CBZ to enter into the systemic circulated described as the mean absorption time were computed from fitted curves. The systemic CBZ clearance (Cl) and area under the plasma concentration–time curve (AUC t 0– ∞ ) from zero to infinity were computed by utilizing the trapezoidal rule . An assumption that the CBZ molecules were completely absorbed from the site of administration of the MCC formulation was made.…”
Section: Methodsmentioning
confidence: 99%